(untitled) (International Journal of Engineering and Computer Science, 2017)
“The MHD flow and convective heat transfer from water functionalized CNTs over a static/moving wedge in the presence of heat source/sing are studied numerically. Thermal conductivity and viscosity of both single and multiple wall carbon nanotubes (CNTs) within a base fluid (water) of similar volume are investigated to determine the impact of these properties on thermo fluid performance. The governing partial differential equations are converted into nonlinear, ordinary, and coupled differential equations and are solved using bvp4c Matlab solver. The effects of volume fraction of CNTs and magnetic and wedge parameters are investigated and presented graphically. The numerical results are compared with the published data and are found to be in good agreement.